Manajemen Sumber Daya Manusia di Era Digital : Tinjauan Literatur Berbasis Perspektif e-HRM dan People Analytics (Jurnal Nirta : Inovasi Multidisiplin, 2026)
The rapid advancement of digital technology has significantly transformed organizational management practices, particularly in Human Resource Management (HRM). Technology-driven HR systems such as Human Resource Information Systems (HRIS), Applicant Tracking Systems (ATS), Learning Management Systems (LMS), and People Analytics platforms have shifted HR functions from administrative roles toward strategic decision-making. This study aims to examine the role of technology and Artificial Intelligence (AI) in the transformation of HRM by reviewing its applications in recruitment, performance management, training and development, employee engagement, and workforce planning. This research employs a qualitative literature review approach by analyzing academic journals, books, and relevant scholarly sources. The findings indicate that AI enhances efficiency, enables predictive workforce analytics, supports personalized learning, and strengthens evidence-based HR decisions. However, AI implementation also presents challenges such as algorithmic bias, data privacy risks, transparency issues, and the potential reduction of human interaction in HR processes. Therefore, organizations must implement ethic governance, transparency mechanisms, and human oversight in AI-driven HR systems. This study contributes to academic discourse by providing a structured conceptual framework of AI adoption in HRM and offering managerial implications for responsible implementation.